Research of caviar vacuum drying processes - Ermolaev V. A.; Bondarchuk O. N.; Makhacheva E. V. (Vestnik MGTU)
Fish caviar is a valuable product with high nutritional and taste qualities. Caviar contains a large amount of protein, which is one of the significant criteria for food products. Essential acids contained in caviar are of particular value. They cannot be synthesized in the human body and enter it only with food. The search for effective ways to preserve red caviar using new types of preservatives, as well as various technologies that ensure the high quality of this product, is a promising direction. The studies conducted by the authors have shown that a possible way to process caviar into a long-term storage product is its drying. Dehydration allows you to significantly extend the shelf life of caviar without adding preservatives. It is worth noting that dried caviar can be ground into powder for adding to other products and enriching them with useful substances. Vacuum drying has been chosen as a method of drying caviar, since it is vacuum drying that can dehydrate food products while maintaining their quality indicators. The paper presents experimental studies that have allowed us to identify the most rational parameters for vacuum drying of caviar: heating temperature of 40 °C, residual pressure of 5 kPa, heat flow density of 3–4 kW/m2, layer thickness of 10–20 mm. With the specified parameters, the drying time is 270–370 min, and the organoleptic assessment is 38–40 points out of 45.